Recent developments and challenges in understanding the Dutch Reformed family of churches’ missional identity and calling - Van der Watt, G. (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The article focuses on recent developments in and discourses on the missionary or missional calling and identity of the Dutch Reformed Church Family. The historical legacy of an ideological missionary approach and involvement, the reaction of younger sister churches, important workshops and declarations, the struggle for unification as well as the post-Apartheid context, contributed significantly to this process of understanding its calling to witness and service. It is a continuing discourse which is currently also impacted by a new understanding of “being” missional congregations.